El sufijo -azo y su traducción al italiano - Sara Bani (MediAzioni)
Derivation is an extremely productive mechanism of lexical innovation in Spanish, which can cause difficulties in translation, even in the case of a related language such as Italian. This article analyses the procedures used to convey in Italian the different meanings of lexemes suffixed with -azo, on the basis of a corpus of Spanish novels and their corresponding translated versions. The aim is to classify, describe and discuss professional translators’ solutions in real-life situations. The context of communication plays a fundamental role in identifying the value of the suffix -azo, which can be an augmentative appreciative or a nominal derivative indicating a sharp contact. The translation may be synthetic, analytical, with a phraseological unit or zero (the suffixed lexeme is not translated); it may or may not present affixation; the semantic load of the suffix may be maintained or lost in translation; the translation may be the result of a generalisation or a specification.